Peningkatan Kemampuan Mendeskripsikan Daur Hidup Hewan Melalui Penggunaan Media Gambar Berseri Pada Siswa Tunarungu Kelas V SLB - Usman, Usman; Mustafa, Mustafa; Ningrum, Khairunnisa Justika (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
This research study focuses on the lack of ability to describe the life cycle of animals in deaf students in science subjects at SLB Negeri 1 Makassar. The method used is classroom kuantitatif aproach. The data collection method applied is a test. The subjects of this study were deaf students in class V SLB Negeri 1 Makassar with the initials MIM. This study has several conclusions, namely: 1) The ability to describe the animal life cycle of deaf students in grade V SLB Negeri 1 Makassar in Baseline  1 (A1) situations is in the very poor category. 2) The ability to describe the animal life cycle of class V deaf students in the intervention situation (B) is in the good category. 3) The ability to describe the animal life cycle of deaf students in class V at Baseline  2 (A2) is in the very good category. 4) The ability to describe the life cycle of animals using serial picture media for deaf students in class V is based on the results of analysis between situations, namely in the Baseline  1 situation (A1) very lacking, in the intervention situation (B) in the good category, and in the Baseline  2 situation (A2) ) is in the very good category.